Scouring of pressure flow through bridge abutments - Nadiah Azman, 1994-, author; Amat Sairin Demun, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017